Can artificial intelligence identify effective COVID‐19 therapies?. Issue 8 (7th July 2020) - Schultz, Michael B; Vera, Daniel; Sinclair, David A
Abstract : In this issue of EMBO Molecular Medicine, Stebbing et al (2020b) validate an artificial intelligence‐assisted prediction that a drug used to treat rheumatoid arthritis could be a potent weapon against COVID‐19. Using liver organoids infected with SARS‐CoV‐2, they confirm dual antiviral and anti‐inflammatory activities and show that its administration in four COVID‐19 patients is correlated with disease improvement, paving the way for more rigorous placebo‐controlled trials. Abstract : As the COVID‐19 pandemic is demonstrating, adversity fosters innovation. Here, the marriage of machine learning and rapid clinical trials provides hope for progress.